Design of Shape Memory Alloy (SMA) Actuators - Rao, Ashwin (Springer, 2016)
This short monograph presents an analysis and design methodology for shape memory alloy (SMA) components such as wires, beams, and springs for different applications. The solid-solid, diffusionless phase transformations in thermally responsive SMA allows them to demonstrate unique characteristics like superelasticity and shape memory effects. The combined sensing and actuating capabilities of such materials allows them to provide a system level response by combining multiple functions in a single material system. In SMA, the combined mechanical and thermal loading effects influence the functionality of such materials.